2020
DOI: 10.21203/rs.3.rs-129625/v1
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

WITHDRAWN: Economic Burden of Non-Alcoholic Steatohepatitis with Significant Fibrosis in Thailand

Abstract: Background: Non-alcoholic steatohepatitis (NASH) has been recognised as a significant form of chronic liver disease and a common cause of cirrhosis and hepatocellular carcinoma, resulting in a considerable financial burden on healthcare resources. Currently, there is no information regarding the economic burden of NASH in low- and middle-income countries (LMICs). The aim of this study was to estimate the economic burden of NASH in Thailand as a lesson learned for LMICs.Methods: To estimate the healthcare costs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Of the 28 articles included in this review, 13 were burden-of-disease studies that did not investigate a particular intervention, of which 6 reported both economic and clinical burden of disease, 19,[27][28][29][30][31] and 7 focused solely on clinical burden of disease. 3,[21][22][23][24][25][26] Eight articles primarily analyzed treatment interventions, 20,[32][33][34][35][36][37][38] of which 1 analyzed a hypothetical treatment.…”
Section: Summary Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 28 articles included in this review, 13 were burden-of-disease studies that did not investigate a particular intervention, of which 6 reported both economic and clinical burden of disease, 19,[27][28][29][30][31] and 7 focused solely on clinical burden of disease. 3,[21][22][23][24][25][26] Eight articles primarily analyzed treatment interventions, 20,[32][33][34][35][36][37][38] of which 1 analyzed a hypothetical treatment.…”
Section: Summary Of Studiesmentioning
confidence: 99%
“…3,[21][22][23][24][25][26] In 3 studies the modeling of NASH/NAFLD was not clearly described. 20,30,40 Six studies explicitly focused on a NASH population. 19,32,35,37,38…”
Section: Nonalcoholic Fatty Liver Disease-nonalcoholic Steatohepatitismentioning
confidence: 99%
“…Notably, the total economic burden of MAFLD is highest in adults aged 45 to 65 years, mirroring disease prevalence and duration in the same age group [16] . In 2019, the total lifetime cost of Thai MeSH patients was estimated to be $15.2 billion [29] …”
Section: Financial and Social Impact Of Mafldmentioning
confidence: 99%
“…In addition to its association with adverse clinical outcomes, NAFLD has been shown to have a negative impact of patient‐reported outcomes (PROs) such as health‐related quality of life, the ability to be physically active as well as work productivity 20–28 Furthermore, the economic burden of NAFLD has been reported to be quite substantial especially among those with NASH and fibrosis 29–34 …”
Section: Introductionmentioning
confidence: 99%
“…Finally, despite these substantial clinical, humanistic and economic burden, awareness about NAFLD among patients and healthcare providers remains low 33–36 . In this context, NAFLD is predominantly discovered incidentally and a systematic guideline to identify NAFLD patients at high risk of progression in the primary care setting is currently lacking.…”
Section: Introductionmentioning
confidence: 99%